TEACHING SUMMARIZATION STRATEGIES - Muhammad Nadjmuddin (Politeknik Negeri Sriwijaya, 2010)
Summary writing is widely used as both a means for assessing student learning as well as a way to use other sources in academic writing. As writing teachers we know that our students have difficulty with summarizing information in an organized and accurate way. In their summaries our students focused on trivial information, or simply copied entire sentences from the source text and gave their own opinions and experiences in their summaries. Unskilled readers may need instruction and practice in summarizing paragraphs; other readers may need instruction and practice in summarizing larger chunks of information. They need an approach to sort information, and they need to see how skilled readers with sufficient background knowledge identify important information and summarize. The difficulty of the materials must be graded so that the students’ strategies and skills can be developed progressively Learning should start from single paragraph level summarizing and work up to section summarization and summarization of entire chapters. Finally, they can summarize from multiple sources. The teacher’s instructional materials and models of how to use an appropriate summarization strategy of various text lengths, content area and complexity will improve the ability of students to summarize. The students’ background knowledge is also important in making judgments about the important information in summarizing.